Functional Annotation of Class I Lysyl-tRNA Synthetase Phylogeny Indicates a Limited Role for Gene Transfer - Ambrogelly, Alexandre (American Society for Microbiology, 2002)
Functional and comparative genomic studies have previously shown that the essential protein lysyl-tRNA synthetase (LysRS) exists in two unrelated forms. Most prokaryotes and all eukaryotes contain a class II LysRS, whereas most archaea and a few bacteria contain a less common class I LysRS. In bacteria the class I LysRS is only found in the α-proteobacteria and a scattering of other groups, including the spirochetes, while the class I protein is by far the most common form of LysRS in archaea. To investigate this unusual distribution we functionally annotated a representative phylogenetic sampling of LysRS proteins. Class I LysRS proteins from a variety of bacteria and archaea were characterized in vitro by their ability to recognize Escherichia coli tRNA(Lys) anticodon mutants. Class I LysRS proteins were found to fall into two distinct groups, those that preferentially recognize the third anticodon nucleotide of tRNA(Lys) (U36) and those that recognize both the second and third positions (U35 and U36). Strong recognition of U35 and U36 was confined to the pyrococcus-spirochete grouping within the archaeal branch of the class I LysRS phylogenetic tree, while U36 recognition was seen in other archaea and an example from the α-proteobacteria. Together with the corresponding phylogenetic relationships, these results suggest that despite its comparative rarity the distribution of class I LysRS conforms to the canonical archaeal-bacterial division. The only exception, suggested from both functional and phylogenetic data, appears to be the horizontal transfer of class I LysRS from a pyrococcal progenitor to a limited number of bacteria.